PERSPECTIVES IN THE APPLICATION OF THE INTERNATIONALE STANDARDS OF SUPREME AUDIT INTSTITUTIONS - Dana Simona Gherai; Ioan Gheorghe Tara; Diana Elisabeta Matica (Annals of the University of Oradea: Economic Science, 2017)
Administrative and financial activities of the public sector are governed by laws and regulations, so public external audit needs to verify that asset accounting and management are properly conducted in accordance with applicable laws and regulations. The public sector becomes the main beneficiary of the application of standards by the Supreme Audit Institutions. Institutions, through their activities, offer a certainty to the public sector that they carry out their activities in good condition and in an economical and efficient way. At the same time, audit activities also provide taxpayers with the good functioning of the public system, and the latter can provide greater confidence to the whole system. In our paper we have identify, for each EU Member State, the standards applied in the public financial audit system. According to the results, most member states apply the International Standards on Auditing or ISSAI, which underlines the desire for harmonization in the public sector. At the same time, the countries that have recently joined the European Union seem to be more interested in reforming the public sector and moreover, reforms in this sector are finalized more rapidly.